Finite element analysis on deformation of stretchable electronic interconnect substrate using polydimethylsiloxanes (PDMS) - Roslan, Muhamad Fahmi Mohd; Shaffiar, Norhashimah; Muhamad Khairussaleh, Nor Khairusshima; Syed Shaharuddin, Sharifah Imihezri (Institute of Physics Publishing, 2018)
. Over the years, the technology of electronic industry has growth tremendously. Open ended research on how to make a better concept of electronic circuit is ongoing especially on the stretchable electronic devices. There are many designs to achieve stretchability in electronic circuits. The problem occurs when deformation applied to the stretchable electronic circuit, it cannot maintain its functionality. Fracture may happen on the conductor. In this research, the study on deformation of stretchable electronic interconnects substrate using Polydimethlysiloxanes is carried out. The purpose of this research are to study the axial deformation occur, to determine the optimum shape of the conductor designs (horseshoe, rectangular and u-shape design) for the stretchable electronic interconnect and to compare the mechanical properties of Polydimethlysiloxanes (PDMS) with Polyurethane (PU) using Finite Element Analysis (FEA). The simulation was done on the FE model of the stretchable circuit with dimension of 2.4 X 2.4 X 0.5 mm. The stretching of the FE model was simulated with the range of elongation at 10, 20 and 30 percent from its original length in order to find the strain value for all three of the conductor designs. The best conductor design is used to simulate with different types of substrate (PDMS and PU). From the simulation result, Horseshoe design record the lowest strain value for each elongation, followed by rectangular and U-shape design. Thus, Horseshoe is considered as the optimum design for the conductor compared to the other two designs. From the result also, it shows that PDMS substrate will offer more maximum allowable stretchability compared to PU substrates. Thus PDMS is considered as a better substrate compare to PU. PDMS is a good material to replace PU since it can perform under tension much better mechanically.